ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
News on various topics, including Liberia's continued subscription to the UN Charter; and Liberia Broadcasting System (LBS) cooperation with Nigeria.
Keywords: News; Public Affairs